2003
DOI: 10.1074/jbc.m309039200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-based Target Identification

Abstract: LAF389 is a synthetic analogue of bengamides, a class of marine natural products that produce inhibitory effects on tumor growth in vitro and in vivo. A proteomicsbased approach has been used to identify signaling pathways affected by bengamides. LAF389 treatment of cells resulted in altered mobility of a subset of proteins on two-dimensional gel electrophoresis. Detailed analysis of one of the proteins, 14-3-3␥, showed that bengamide treatment resulted in retention of the amino-terminal methionine, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 36 publications
3
90
0
4
Order By: Relevance
“…Although we have shown that pyridine-2-carboxylic acid derivatives selectively inhibit HsMetAP1 in vitro and block cell proliferation in culture, the causative relationship between these two effects remained to be established. As the first step to assess this relationship, we determined whether pyridine-2-carboxylic acid derivatives are capable of entering cells and inhibiting HsMetAP1 activity in vivo by examining the N-terminal initiator methionine status of a known protein substrate, 14-3-3␥ (11). HeLa cells were incubated with various concentrations of compound 1 for 24 h before they were harvested for Western blot with a monoclonal antibody (clone HS23) specific for the methionylated N-terminal fragment of 14-3-3␥ protein (11).…”
Section: Hsmetap1-specific Inhibitors Block Proliferation Of Tumor Cementioning
confidence: 99%
See 1 more Smart Citation
“…Although we have shown that pyridine-2-carboxylic acid derivatives selectively inhibit HsMetAP1 in vitro and block cell proliferation in culture, the causative relationship between these two effects remained to be established. As the first step to assess this relationship, we determined whether pyridine-2-carboxylic acid derivatives are capable of entering cells and inhibiting HsMetAP1 activity in vivo by examining the N-terminal initiator methionine status of a known protein substrate, 14-3-3␥ (11). HeLa cells were incubated with various concentrations of compound 1 for 24 h before they were harvested for Western blot with a monoclonal antibody (clone HS23) specific for the methionylated N-terminal fragment of 14-3-3␥ protein (11).…”
Section: Hsmetap1-specific Inhibitors Block Proliferation Of Tumor Cementioning
confidence: 99%
“…There has also been circumstantial evidence implicating a role of HsMetAP1 in tumor cell proliferation. By using a proteomics-based approach, both human MetAPs were identified as the binding targets of bengamides, a class of marine natural products that inhibit tumor growth in vitro and in vivo (11). Recently, pyridinyl pyrimidines have also been identified as nonselective inhibitors for MetAPs, and inhibit the proliferation of tumor cell lines (12).…”
mentioning
confidence: 99%
“…The human type II MetAP is a target of the antiangiogenic compounds fumagillin, ovalicin, and TNP-470 (6)(7)(8). Bengamides inhibit both types of MetAP (9) and cause inhibition of the growth of several human tumor cell lines in vitro at low-nanomolar concentrations. Therefore, human MetAPs may also serve as targets for the development of new anticancer agents.…”
mentioning
confidence: 99%
“…Proteomics-based approaches can also be used to identify the molecular targets of compounds with unknown mechanism of action. For example, the elusive target of LAF-389 was identified by 2-D PAGE approach via molecular changes in expression of cellular proteins following treatment of cell culture with this drug [114,115]. LAF-389 is a synthetic analog of bengamide B possessing antitumor activity.…”
Section: Pharmacoproteomicsmentioning
confidence: 99%